2019
DOI: 10.3390/toxins11080467
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Profiling of Aspergillus Isolates with Varying Aflatoxin Production Potential from Different Maize-Growing Regions of Kenya

Abstract: Highly toxigenic strains of Aspergillus flavus have been reported to frequently contaminate maize, causing fatal aflatoxin poisoning in Kenya. To gain insights into the environmental and genetic factors that influence toxigenicity, fungi (n = 218) that were culturally identified as A. flavus were isolated from maize grains samples (n = 120) from three regions of Kenya. The fungi were further characterized to confirm their identities using a PCR-sequence analysis of the internal transcribed spacer (ITS) region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…The aflR and aflD peaked at 6 and 9 dpi, respectively. AflD is an early gene encoding a reductase responsible for the conversion of norsolorinic acid to averantin [45][46][47]. The temporal shift of three days observed in this study analysing aflR and aflD transcriptional profiles could be due to the role of aflR that, being a transcription activator of the aflatoxin biosynthetic pathway, was earlier induced, and showed a higher magnitude of activation in comparison to aflD.…”
Section: Discussionmentioning
confidence: 61%
“…The aflR and aflD peaked at 6 and 9 dpi, respectively. AflD is an early gene encoding a reductase responsible for the conversion of norsolorinic acid to averantin [45][46][47]. The temporal shift of three days observed in this study analysing aflR and aflD transcriptional profiles could be due to the role of aflR that, being a transcription activator of the aflatoxin biosynthetic pathway, was earlier induced, and showed a higher magnitude of activation in comparison to aflD.…”
Section: Discussionmentioning
confidence: 61%
“…Aspergillus was the most common fungi in the gut of organisms Aspergillus minisclerotigenes produced mycotoxin, , which exerted neurotoxic effects on brain tissues . Recent evidence demonstrated that inhalation of Aspergillus variegatus could induce neuroinflammation, destroyed neuroimmune homeostasis, and led to cognitive and emotional defects in children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetically, during studies of endophytic fungi as sources of bioactive metabolites, molecular identification is typically performed using the ITS sequences or GenBank BLAST search ( Raja et al, 2017 ; Zhang X. G. et al, 2020 ). However, the two approaches have distinct limitations, because they may not be able to distinguish some members with close phylogenetic relationships of certain genera ( Oloo et al, 2019 ), and more than 1/4 GenBank fungal ITS sequences were submitted without sufficient taxonomic confirmation ( Raja et al, 2017 ). Therefore, in this study, molecular identification was carried out using protein-coding and ribosomal genes, mainly including LSU, ITS, and TUB.…”
Section: Discussionmentioning
confidence: 99%